SISTEM MONITORING MULTI REMOTE-SENSOR NIRKABEL: STUDI KASUS MONITORING TEMPERATUR DAN KELEMBABAN 01 RUANG TERBUKA/TERTUTUP - Alvano Yulian (BATAN, 2013)
The system which was arranged is for telemetry system with two ways communication bet-ween